Sustainable risk management practice in the organization a Malaysian case study - Siti Afiqah Zainuddin; Borhan Abdullah; Noorul Azwin Md Nasir; Tahirah Abdullah (Springer Science and Business Media Deutschland GmbH, 2022)
Businesses are becoming more conscious of operational risk management practices due to the COVID-19 pandemic. However, some firms practice risk management without fully comprehending how it might help them and their needs. As a result, companies that practice risk management without realizing it are being controlled by the discipline itself. The goal of this study is to look into the epistemic process of risk management practice in the workplace. This phenomenological study interviewed 39 risk management officers, executives, and employees. Data are thematically analyzed. This study discovered five epistemic processes of risk mapping using Foucault’s governmentality paradigm. This phenomenological study, interestingly, revealed the black box of risk management practices, as well as the behavior of risk management officers, executives, and risk owners who preferred to monitor the compliance aspects of risk management practices rather than comprehend the capabilities of risk management that could be used within their strategic planning process. Unaware of this black box, organizational actors were blanketed by the organization’s culture of fear, which created the impression that the authority was always watching every word said and every action taken. Practically, this study contributes an improved understanding of the real function of risk management that helps them justify the practice and reduce unnecessary fear. The paper concludes with limitations and research recommendations.